Regulation of angiogenic growth factor expression by hypoxia, transition metals, and chelating agents. - Gleadle, J; Ebert, B; Firth, J; Ratcliffe, P (1995)
Recent work has indicated that oxygen-sensing mechanism(s) resembling those controlling erythropoietin production operate in many non-erythropoietin-producing cells. To pursue the implication that such a system might control other genes, we studied oxygen-regulated expression of mRNAs for vascular endothelial growth factor, platelet-derived growth factor (PDGF) A and B chains, placental growth factor (PLGF), and transforming growth factor in four different cell lines and compared the characteristics with those of erythropoietin regulation. Oxygen-regulated expression was demonstrated for each gene in at least one cell type. However, the response to hypoxia (1% oxygen) varied markedly, ranging from a 13-fold increase (PDGF-B in Hep G2 cells) to a 2-fold decrease (PLGF in the trophoblastic line BeWo). For each gene/cell combination, both the magnitude and direction of the response to hypoxia were mimicked by exposure to cobaltous ions or two different iron-chelating agents, desferrioxamine and hydroxypyridinones. These similarities with established characteristics of erythropoietin regulation indicate that a similar mechanism of oxygen sensing is operating on a variety of vascular growth factors, and they suggest that chelatable iron is closely involved in the mechanism.